2008
DOI: 10.1002/chem.200801247
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Host–Guest Complexes: Directing the Supramolecular Structure through Secondary Host–Guest Interactions

Abstract: A set of four hybrid host-guest complexes based on the inorganic crown ether analogue [H12W36O120]12- ({W36}) have been isolated and characterised. The cluster anion features a central rigid binding site made up of six terminal oxygen ligands and this motif allows the selective binding of a range of alkali and alkali-earth-metal cations. Here, the binding site was utilised to functionalise the metal oxide-based cavity by complexing a range of protonated primary amines within the recognition site. As a result, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 62 publications
(98 reference statements)
4
17
0
Order By: Relevance
“…Within the observed tendency of 3.34 to 3.83 emu K mol −1 , there is no clear correlation between the magnetic properties and the nature of the frameworks, which include different cations interacting with the polyanions, even though it is clear that the interactions between the different cations and the polyanion in the lattice affect the magnitude of the exchange phenomena in the cluster. It is interesting to point out that Hermosilla-Ibáñez et al reported in 2014 that it is possible to show by DFT calculations that the alkaline ions in compounds (18) and (19) quench the intracluster antiferromagnetic coupling, in comparison with compound (5) [57]. In this study, the results indicated that the presence of alkaline ions perturbs the extent of the spin density of the magnetic orbitals (dxy); this perturbation is dependent on the distance between the alkaline cation and the oxygen of the vanadyl groups.…”
Section: Magnetic Propertiesmentioning
confidence: 93%
See 3 more Smart Citations
“…Within the observed tendency of 3.34 to 3.83 emu K mol −1 , there is no clear correlation between the magnetic properties and the nature of the frameworks, which include different cations interacting with the polyanions, even though it is clear that the interactions between the different cations and the polyanion in the lattice affect the magnitude of the exchange phenomena in the cluster. It is interesting to point out that Hermosilla-Ibáñez et al reported in 2014 that it is possible to show by DFT calculations that the alkaline ions in compounds (18) and (19) quench the intracluster antiferromagnetic coupling, in comparison with compound (5) [57]. In this study, the results indicated that the presence of alkaline ions perturbs the extent of the spin density of the magnetic orbitals (dxy); this perturbation is dependent on the distance between the alkaline cation and the oxygen of the vanadyl groups.…”
Section: Magnetic Propertiesmentioning
confidence: 93%
“…From the χT(T) graph reported by Zhou et al [53] it is possible to infer that (27) is almost magnetically uncoupled at room temperature. On the other hand, the χT values of the rest of compounds, (5), (12), (15), (18), and (19) show that all of them are magnetically coupled at room temperature. Within the observed tendency of 3.34 to 3.83 emu K mol −1 , there is no clear correlation between the magnetic properties and the nature of the frameworks, which include different cations interacting with the polyanions, even though it is clear that the interactions between the different cations and the polyanion in the lattice affect the magnitude of the exchange phenomena in the cluster.…”
Section: Magnetic Propertiesmentioning
confidence: 97%
See 2 more Smart Citations
“…[12,13] In this initial study, the electrostatically-controlled formation of organic-inorganic hybrid systems was investigated with a range of experimental and theoretical analyses. The aim was to identify ways of directing the self-assembly so as to guide the resulting architecture into separate hydrophilic and hydrophobic regions.…”
Section: Introductionmentioning
confidence: 99%